Risk Factors for Local Failure Following Chemoradiation and Magnetic Resonance Image–Guided Brachytherapy in Locally Advanced Cervical Cancer: Results From the EMBRACE-I Study. Issue 10 (1st April 2023) - Schmid, Maximilian P.; Lindegaard, Jacob C.; Mahantshetty, Umesh; Tanderup, Kari; Jürgenliemk-Schulz, Ina; Haie-Meder, Christine; Fokdal, Lars U.; Sturdza, Alina; Hoskin, Peter; Segedin, Barbara; Bruheim, Kjersti; Huang, Fleur; et al.
Abstract : PURPOSE: To report clinical and treatment characteristics, remission and failure patterns, and risk factors for local failure (LF) from the EMBRACE-I study. MATERIALS AND METHODS: EMBRACE-I was a prospective, observational, multicenter cohort study on magnetic resonance imaging–based image-guided adaptive brachytherapy (MR-IGABT) in locally advanced cervical cancer. Treatment consisted of external beam radiotherapy, concurrent chemotherapy, and MR-IGABT. LF was defined as progressive or recurrent disease in the cervix, uterus, parametria, pelvic wall, or vagina. Competing risk analysis was used to estimate local tumor control (LC) and Cox proportional regression models for multivariable analysis and dose-response analysis. RESULTS: One thousand three hundred eighteen patients with a median follow-up of 52 months were available for this analysis. Eighty-one patients had persistent disease 3 months after end of treatment. Of those, 60 patients achieved LC at 6-9 months without further treatment, whereas 21 patients had progressive disease. In addition, 77 patients developed a local recurrence after complete remission comprising a total number of 98 LFs. LFs were located inside the MR-IGABT target volumes in 90% of patients with LF. In multivariable analysis, histology, minimal dose to 90% of high-risk clinical target volume (CTVHR ), maximum tumor dimension, CTVHR > 45 cm 3, overall treatment time, tumor necrosis on magnetic resonance imaging at diagnosis, uterine corpus infiltration at diagnosis and at MR-IGABT, and mesorectal infiltration at MR-IGABT had significant impact on LF. Dose-response analysis showed that a minimal dose to 90% of 85 Gy to the CTVHR led to 95% (95% CI, 94 to 97) LC 3 years postintervention for squamous cell in comparison to 86% (95% CI, 81 to 90) for adeno/adenosquamous carcinoma histology. CONCLUSION: The present study demonstrates the safety and validity of the GYN GEC-ESTRO/ICRU-89 target concept and provides large-scale evidence for dose prescription and new risk factors for LF in MR-IGABT in locally advanced cervical cancer.